2017
DOI: 10.1080/2162402x.2017.1313369
|View full text |Cite
|
Sign up to set email alerts
|

Innate γδT17 cells play a protective role in DSS-induced colitis via recruitment of Gr-1+CD11b+ myeloid suppressor cells

Abstract: Innate γδ T cells play critical roles in mucosal immunity such as regulating intestinal epithelial homeostasis. In addition, γδ T cells are significantly increased in the inflamed mucosa of patients with ulcerative colitis. However, γδ T cells are a heterogeneous population. IL-17-producing versus IFNγ-producing γδ T cells play differential roles in different disease settings. Therefore, dissecting the exact role of different subsets of γδ T cells in colitis is essential for understanding colitis immunopathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Vγ2 cells, whose most striking feature is the secretion of IL-17A, are involved in immune responses and various diseases. They not only play protective roles against colitis and viruses, but also promote liver fibrosis [16,48], especially, γδ T cells could exacerbate liver fibrosis by aiding the activation of HSCs in liver fibrosis induced by carbon tetrachloride injection [49]. Our observations show that during infection, the increase in Vγ2 cells was accompanied by an increase in their secreted IL-17A.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Vγ2 cells, whose most striking feature is the secretion of IL-17A, are involved in immune responses and various diseases. They not only play protective roles against colitis and viruses, but also promote liver fibrosis [16,48], especially, γδ T cells could exacerbate liver fibrosis by aiding the activation of HSCs in liver fibrosis induced by carbon tetrachloride injection [49]. Our observations show that during infection, the increase in Vγ2 cells was accompanied by an increase in their secreted IL-17A.…”
Section: Discussionmentioning
confidence: 64%
“…As a member of the IL-17 family, IL-17A is involved in various biological processes by binding its cognate receptor, IL-17RA [10][11][12][13]. Accumulating evidence demonstrates that IL-17A is related to a variety of inflammatory and autoimmune diseases such as inflammatory bowel diseases (IBD) and multiple sclerosis [14][15][16]. Multiple studies have demonstrated that Th17 cells, natural killer T cells and γδ T cells produce IL-17A [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of IL-17 could activate Act-1 (a key adaptor protein of IL-17 receptor), which attenuated inflammation and immobilized the localization of occluding (a tight junction protein) to prevent excessive intestinal permeability (Figure 2 ) ( 68 ). Another crucial anti-inflammatory pathway of γδ T cells is linked to the recruitment of MDSCs ( 29 ). Sun et al observed that TCRγδ-deficient mice were more susceptible to dextran sulfate sodium-induced colitis, with a reduced expression of IL-18 and CXCL5 relative to wild-type mice, which was important for the subsequent Gr-1 + CD11b + suppressor cell infiltration ( 29 ).…”
Section: Participation Of γδ T Cells In Chronic Inflammationmentioning
confidence: 99%
“…Another crucial anti-inflammatory pathway of γδ T cells is linked to the recruitment of MDSCs ( 29 ). Sun et al observed that TCRγδ-deficient mice were more susceptible to dextran sulfate sodium-induced colitis, with a reduced expression of IL-18 and CXCL5 relative to wild-type mice, which was important for the subsequent Gr-1 + CD11b + suppressor cell infiltration ( 29 ). Moreover, mice reconstituted with γδT17 cells (mainly Vγ6) had ameliorated intestinal inflammation and were associated with increased frequency of Gr-1 + CD11b + cells, whereas mice with IFN-γ producing γδ T cells had no significant difference, indicating a protective role of γδT17 cells (but not IFN-γ producing γδ T cells) to a certain extent ( 29 ).…”
Section: Participation Of γδ T Cells In Chronic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation